The effect of salinity on growth and ion accumulation in six turfgrass species - Md. Kamal Uddin; Abdul Shukor Juraimi; Mohd Razi Ismail; Md. Amirul Alam (Southern Cross Publishing and Printing Pty Ltd, 2012)
The objective of this study was to evaluate the effect of salinity on the growth and ion accumulation in six turfgrass species namely Paspalum vaginatum, Zostera japonica, Zostera matrella, Digitaria didcatyla, Cynodon dactyon cv ‘Satiri’, and Cynodon dactylon cv ‘Tifdwarf’. Six salinity levels were applied with electrical conductivity of 0, 88, 176, 264, 352, 440 and 528 mM (sea water). At the highest salinity level (528 mM), the least shoot dry weight reduction was observed in P. vaginatum (40%) compared to control treatment, followed by C. dactylon ‘satiri’ (44%) and Z. japonica (48%). While at this salinity level, maximum shoot reduction was recorded for Z. matrella (55%) followed by C. dactylon ‘Tifdwarf’ (53%). At the highest salinity (528 mM), root dry weight reduction was also least in P. vaginatum (23%) followed by Z. japonica (29%), while the highest recorded in C. dactylon ‘Tifdwarf’ (44%) followed by D. didactyla (39%). Increasing the salinity level decreased the K⁺, Ca⁺⁺, Mg⁺⁺ content and K/Na ratio but increased Na+ content in the shoot and root tissues. P. vaginatum was the less Na⁺ accumulating species at all salinity levels followed by Z. japonica and Z. matrella, while C. dactylon ‘tifdwarf’ was the highest Na⁺ accumulating species followed by D. didactyla and C. dactylon ‘satiri’. P. vaginatum was among the least K⁺ reducing species at all salinity levels followed by Z. japonica and Z. matrella, while the highest K+ reducing species was D. didactyla followed by C. dactylon ‘tifdwarf’ and C. dactylon ‘satiri’. The highest K⁺ /Na⁺ ratios at all salinity levels were recorded in P. vaginatum followed by Z. japonica and Z. matrella.